Evolution of Public Libraries in West Bengal, India: Role of the Britishers, Library Associations and Contemporary Political Parties. Issue 2 (11th May 2022) - Munshi, Shamim Aktar; Ansari, Mehtab Alam
Abstract: This study traces the genesis of public libraries during the British period; the birth of National Library in India; the growth of public libraries in different districts of West Bengal; contributions of different movements in the evolution of West Bengal Public Library System and the role of Left Front government in the enactment of the West Bengal Public Library Act. The purpose of this paper is to review the significant contributions of the Britishers, European missionaries, social reformers and political parties particularly parties having left ideology in the development of public libraries in the West Bengal province of India. The paper investigates the evolution of public libraries for which authors have consulted literature published in different sources. Some of the important documents collected for this study are Annual Reports being published from the Department of Mass Education Extension and Library Services, Government of West Bengal; Census of India, etc. Apart from these sources, some other primary sources have also been used for this paper. This study contributes to have an insight knowledge in order to understand the gradual development of Public Library System in West Bengal.